(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Stroke is one of the leading causes of mortality and long-term disability worldwide. Altered lipid metabolism plays an important role in the development of atherosclerosis and ischemic cerebrovascular disease. Dyslipidaemia is considered a major modifiable risk factor for acute cerebral ischemia. This study was conducted to evaluate the association between lipid profile abnormalities and acute cerebral ischemia. Methodology: This hospital-based observational study was conducted in the Department of Emergency Medicine at Sree Mookambika Institute of Medical Sciences, Kulasekharam, from June 2025 to March 2026. Fifty patients aged between 40 and 80 years with CT/MRI confirmed ischemic or hemorrhagic stroke were included. Patients with liver disease, hypothyroidism, familial hypercholesterolemia, coagulation disorders, trauma, and those on lipid-lowering drugs were excluded. Fasting lipid profile and carotid intima-media thickness (CIMT) were assessed. Statistical analysis was performed using SPSS version 25.0, and p<0.05 was considered statistically significant. Result: Among the study population, 66% had elevated total cholesterol, 72% had high LDL, 72% had elevated triglycerides, and 66% had low HDL levels. Significant association was observed between diabetes mellitus and elevated total cholesterol, triglycerides, and LDL levels (p=0.001). Increased CIMT was observed in a majority of patients. Conclusion: Altered lipid metabolism is strongly associated with acute cerebral ischemia. Early identification and management of dyslipidaemia may reduce stroke-related morbidity and mortality.